Vegetative propagation of coffee by mini-cutting - Rezende, Tiago Teruel; Carvalho, Samuel Pereira de; Bueno Filho, Júlio Sílvio de Sousa; Honda Filho, Cássio Pereira; Simões, Luana de Cássia; Paulino, Ricardo Nascimento Lutfala; Oliveira, Leonardo Luiz; Nascimento, Thales Lenzi Costa (Coffee Science - ISSN 1984-3909, 2017)
The introduction of methods that allow the cloning of coffee plants can be useful in breeding programs and for the commercial production of seedlings. Among the methods for vegetative propagation, cutting has allowed the cloning of coffee plants. However, one of the obstacles for commercial production is the reduced amount of orthotropic branches produced by the matrix plant. An alternative would be the use of mini-cutting, widely used in the production of eucalyptus seedlings. With this work, we aimed at studying the employment of the mini-cutting technique for the formation of clonal seedlings of Coffea arabica L. in tubes of different volumes. We evaluated five types of mini-cuttings performed on different portions of the orthotropic branch (apical, semi-apical, intermediate, semi-basal and basal) and two volumes of tubes (50 and 120 cm3). The experiment was comprised of 10 treatments in a 5x2 factorial scheme, in a completely randomized design, with four replicates. We verified differences only between the types of mini-cuttings. The mini-cuttings performed on the semi-apical, intermediate and semi-basal portions of the orthotropic branches provided better growth for the clonal seedlings, regardless of the volume of the tube used.